Gender-Based Violence in Girls' Sports - Erin Willson; Gretchen Kerr (MDPI AG, 2023)
Millions of girls and young women participate in organized sports annually as a vehicle for developing a strong sense of self, social bonds, a positive body image and a sense of agency. Although the benefits of sport engagement are experienced by many girls, the overwhelming evidence of experiences of gender-based violence in sport cannot be ignored (e.g., USA Gymnastics, Hockey Canada). This paper will address gender-based violence experienced by adolescents in sport with a focus on psychological violence. The literature is replete with evidence that girls experience higher rates of gender-based psychological violence in sport than boys, and as a result, incur developmental costs. Psychological violence is experienced by girls in sport in the form of demeaning comments, body shaming, inequitable media coverage and funding and the ongoing policing of women's bodies in sport through sexualized sport attire and physiological testing. The causes and effects of psychological violence will be addressed along with recommendations to prevent and address gender-based violence in sport.